1997
DOI: 10.1164/ajrccm.156.4.9703012
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Colchicine as an Alternative to Inhaled Corticosteriods in Moderate Asthma

Abstract: Colchicine demonstrates an array of anti-inflammatory properties of potential relevance to asthma. However, the efficacy of colchicine as an alternative to inhaled corticosteroid therapy for asthma is unknown. Five centers participated in a controlled trial testing the hypothesis that in patients with moderate asthma needing inhaled corticosteroids for control, colchicine provides therapeutic benefit as measured by maintenance of control when inhaled steroids are discontinued. Subjects were stabilized on triam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…Although the prevalence of asthma is not significantly different in patients with FMF, we can say that previous studies concluded that colchicine had no treatment effect on asthma. 18 Because colchicine does not have an antiallergic action we do not believe that the decreased atopic sensitisation was due to the treatment. The presented results show that personal atopy in the patients and allergic diseases in the parents, who were accepted as obligate carriers, were indeed lower.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of asthma is not significantly different in patients with FMF, we can say that previous studies concluded that colchicine had no treatment effect on asthma. 18 Because colchicine does not have an antiallergic action we do not believe that the decreased atopic sensitisation was due to the treatment. The presented results show that personal atopy in the patients and allergic diseases in the parents, who were accepted as obligate carriers, were indeed lower.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine (0.5 mg twice daily) reduced clinical score in 10 asthmatic patients, can partially inhibit immunoglobulin E (IgE)-mediated early and late airway responses (Schwarz et al, 1990), and incidence of asthma was significantly lower in patients with familial Mediterranean fever relative to an age-matched adolescent population (Adaliogul et al, 1994), suggesting a therapeutic potential. However, in a larger definitive study, colchicine was demonstrated to have no effect on moderate asthma (Fish et al, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…Les résultats d'une étude avec un antihistaminique H 1 , la chlorphéniramine, également agoniste des récepteurs TAS2R (dont les sous-types 10 et 14) [9] sont aussi évocateurs de propriétés bronchodilatatrices de cette molé-cule [39]. En revanche, une autre étude dont l'objectif était d'évaluer si la colchicine (agoniste TAS2R4, 39 et 46) pouvait être une alternative aux corticostéroïdes n'a pas montré d'effet bronchodilatateur, vraisemblablement en raison de la faible dose administrée (0,6 mg × 2) liée à la toxicité intrinsèque de la molécule et ne permettant pas l'obtention de concentrations suffisantes au niveau du site d'action [40].…”
Section: éTude De La Fonction Respiratoire Dans Les Essais Cliniques unclassified